5D-Black Hole Solution in Einstein-Yang-Mills-Gauss-Bonnet Theory - Mazharimousavi, S. Habib; Halilsoy, Mustafa (Physical Review D, American Physical Society (APS), 2007)
By adopting the 5D version of the Wu-Yang Ansatz we present in closed form a black hole solution in the Einstein-Yang-Mills-Gauss-Bonnet (EYMGB) theory. In the EYM limit, we recover the 5D black hole solution already known.
The file in this item is the publisher version (published version) of the article.
Keywords: gravity; general relativity; 5D-Black Hole Solution; Einstein-Yang-Mills-Gauss-Bonnet Theory